Measuring mathematics self-efficacy as a learning outcome - Pampaka, Maria; Kleanthous, Irene; Hutcheson, Graeme D.; Wake, Geoff (Research in mathematics education, 2011)
We report the construction and validation of a self-report 'Mathematics self-efficacy (MSE)' instrument, designed to measure this construct as a learning outcome of students following post-compulsory mathematics programmes. The sample ranged across two programmes: a traditional preparation for university study in mathematical subjects (Advanced level) and an innovative 'modelling'-based programme intended to widen participation in mathematics through use of technology and coursework. We report Rasch measurement and Generalised Linear modelling analyses of large scale survey data, and occasionally we draw on learners' interviews for triangulation. We found that MSE is related to students' mathematical attainment and gender, as well as their dispositions to further study mathematics. We also show significant differences between students' development of MSE in the two programmes. In conclusion, we propose that MSE deserves further attention as a measure of valued learning outcomes.